A randomized trial to evaluate the pharmacokinetics, pharmacodynamics, and safety of vadadustat in patients with anemia associated with chronic kidney disease receiving hemodialysis - Pamela Navarro-Gonzales; Ajit Chavan; Don Wang; Steven K. Burke; Kevin Dykstra (BMC Nephrology)
Abstract Background Vadadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor for treatment of anemia in dialysis-dependent chronic kidney disease (CKD) with a starting dose of 300 mg once daily (dose adjustments up to 600 mg). A recent phase 1b study evaluated the pharmacokinetics, pharmacodynamics, and safety of higher vadadustat doses (500–900 mg) in healthy volunteers. Here we report the pharmacokinetic (PK), pharmacodynamic (PD), and safety characterization of higher doses of vadadustat in patients with CKD receiving dialysis. Methods This phase 1b, randomized, open-label study evaluated the pharmacokinetics and pharmacodynamics of vadadustat (600, 750, or 900 mg) in patients with CKD-related anemia receiving hemodialysis over a 10-day treatment period. Forty-six eligible patients were randomized to vadadustat 600, 750, or 900 mg daily or an intravenous erythropoiesis-stimulating agent. For vadadustat groups, blood samples for PK and PD analyses were collected on Day 1 and Day 8. PK analyses included area under the plasma concentration time curve (AUC) from dosing to last quantifiable concentration and to infinity, and to maximum plasma concentration (Cmax). PD analyses measured serum erythropoietin (EPO), hemoglobin, and red blood cells (RBCs). Safety assessments included adverse events in the safety population (patients who received ≥ 1 dose of study drug). Patients underwent a 30-day safety follow-up period after the last dose of study drug. Results In the vadadustat groups, a dose-dependent increase in plasma exposure of vadadustat (Cmax and AUC) with modest accumulation was observed on Day 1 and Day 8. Vadadustat increased plasma EPO concentrations, with a variable EPO response observed in each group. Relative to baseline, mean hemoglobin and RBC levels remained unchanged, with no significant changes observed in any treatment group. Vadadustat was welltolerated. Conclusions The current study characterized the PK and PD response (EPO and reticulocytes) and safety profile of vadadustat at doses of 600, 750, and 900 mg in patients with CKD receiving dialysis. Overall, vadadustat was well tolerated. These findings will contribute to the development of higher-dose regimens for further investigation in phase 3 studies. Trial Registration ClinicalTrials.gov ID NCT03992066; https://clinicaltrials.gov/study/NCT03992066 ; Retrospectively registered on June 18, 2019. Accessed January 13, 2025.